UNDERSTANDING MALAY ELDERLY’S EMOTION IN CONSUMPTION EXPERIENCE OF SOCIAL SUPPORT AND LIFE SATISFACTION FROM ISLAMIC PERSPECTIVES. - DERAHMAN, ROSMANIZAH (2021)
The elderly population is increasing around the world which witnessing most countries have reached an aging population. This situation leads to a social phenomenon when the life of the elderly becomes more challenging. Among the challenging phenomena is the social support concerning on elderly as well as their social well-being especially on their emotion. Building on existing work, this phenomenology study aims to understand social marketing in a small context of the Malay elderly’s life phenomenon who stay at home regardless of various available institutional care. This study emphasizes exploring their emotion in the consumption experience of their social support and life satisfaction. In this context, an analysis of 18 informants reveals that routine and giving behaviour gives meaning to these elderly significantly.